Differentiation of MSC and annulus fibrosus cells on genetically engineered silk fleece‐membrane‐composites enriched for GDF‐6 or TGF‐β3. Issue 5 (22nd November 2017) - Frauchiger, Daniela A.; Heeb, Silvan R.; May, Rahel D.; Wöltje, Michael; Benneker, Lorin M.; Gantenbein, Benjamin
ABSTRACT: Intervertebral disc (IVD) repair is a high‐priority topic in our active and increasingly ageing society. Since a high number of people are affected by low back pain treatment options that are able to restore the biological function of the IVD are highly warranted. Here, we investigated whether the feasibility of genetically engineered (GE)‐silk from Bombyx mori containing specific growth factors to precondition human bone‐marrow derived mesenchymal stem cells (hMSC) or to activate differentiated human annulus fibrosus cells (hAFC) prior transplantation or for direct repair on the IVD. Here, we tested the hypothesis that GE‐silk fleece can thrive human hMSC towards an IVD‐like phenotype. We aimed to demonstrate a possible translational application of good manufacturing practice (GMP)‐compliant GE‐silk scaffolds in IVD repair and regeneration. GE‐silk with growth and differentiation factor 6 (GDF‐6‐silk) or transforming growth factor β3 (TGF‐β3, TGF‐β3‐silk) and untreated silk (cSilk) were investigated by DNA content, cell activity assay and glycosaminoglycan (GAG) content and their differentiation potential by qPCR analysis. We found that all silk types demonstrated a very high biocompatibility for both cell types, that is, hMSC and hAFC, as revealed by cell activity, and DNA proliferation assay. Further, analyzing qPCR of marker genes revealed a trend to differentiation toward an NP‐like phenotype looking at the Aggrecan/Collagen 2 ratio which was around 10:1. Our results support the conclusion that our GE‐silk scaffold treatment approach can thrive hMSC towards a more IVD‐like phenotype or can maintain the phenotype of native hAFC. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:1324–1333, 2018. Abstract : Genetically enriched silk fleece scaffolds were produced by transduction of Bombyx mori larvae with a baculovirus construct containing GDF6 or TGFb3. Silk fleeces were produced under GMP‐compliant conditions for the purpose of intervertebral disc repair. We found that these sericine‐free GMP silk scaffolds were highly cytocompatible and that primary human bone‐marrow derived stem cells can be differentiated towards intervertebral‐like cells as obtained by qPCR and monitoring aggrecan and collagen type 2 ratio.